2014
DOI: 10.1186/1472-6882-14-322
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the effect of the active compound of green tea (EGCG) on the proliferation of peripheral blood mononuclear cells

Abstract: BackgroundCancer immunotherapy requires proper manipulation of the immune system, lymphocytes in particular, in order to identify and destroy the cancer cells as non-self. In this study we investigated the effect of the flavonoid present in green tea, namely epigallocatechin-3-gallate (EGCG), on the proliferation of, and IFN-γ production by, peripheral blood mononuclear cells (PBMC) from breast cancer patients stimulated with a mitogen, anti-CD3 and the common breast cancer peptides Her-2/neu, and p53.MethodsB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 45 publications
(39 reference statements)
0
18
0
Order By: Relevance
“…From an immune perspective, EGCG significantly suppressed IFN-γ production and the proliferation of peripheral blood mononuclear cells in vitro [465]. It was also shown to exert antitumor effects on colorectal cancer cells, at least in part by inhibiting the expression and function of IDO through the suppression of STAT1 activation [466].…”
Section: Low Toxicity Approachesmentioning
confidence: 99%
“…From an immune perspective, EGCG significantly suppressed IFN-γ production and the proliferation of peripheral blood mononuclear cells in vitro [465]. It was also shown to exert antitumor effects on colorectal cancer cells, at least in part by inhibiting the expression and function of IDO through the suppression of STAT1 activation [466].…”
Section: Low Toxicity Approachesmentioning
confidence: 99%
“…PBMC viability in culture medium alone was in the range of 99-100%, BTMFA treatment in the range of 90-100% viability (Figure 3(A1-A3)), and BTMFB treated in the range of 84-86% viability after 48 h (Figure 3(B1-B3)). Pure catechin treatment with PBMC revealed the decreasing cell viability of unstimulated PBMCs [31,32]. Similarly, other studies have also reported that T cell proliferation was inhibited by catechin through inhibiting T cell division and cell cycle progression in a dose-dependent manner in vitro [33].…”
Section: Effect Of Biotransformed Catechin Metabolites On the Cell Pomentioning
confidence: 80%
“…Kaempferol inhibited the activation and proliferation of mouse T lymphocytes in response to ConA, arresting cell cycle at S phase and G2/M in vitro (Mu et al 2009). In humans, green tea catechin EGCG significantly suppressed in vitro lymphocyte proliferation in response to stimulation and IFN gamma production (Saleh et al 2014). Recent studies have shown that green tea catechin, EGCG, affects the differentiation of najve T cells into different effector subsets (Pae and Wu 2013).…”
Section: Discussionmentioning
confidence: 99%